ANALISIS FAKTOR YANG MEMPENAGRUHI PASAR MODAL DAN PEREKONOMIAN DI INDONESIA - Yoki Wesya; Hasdi Aimon; Ariusni Ariusni (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This research aims to knows impact of composite stock price index, exchange rate and value of traded share to capital market and analyze the impact of capital market to indonesia’s economics using two stage least squares (TSLS). The first equation to seek the impact of composite stock price index, exchange rate dan and value of traded share to capitalism stock. The results of this research showed composite stock price index, exchange rate, value of traded share have significant positive impact to capitalism stock.. The second equation to seek the impact of consumption, government expenditure, capitalism stock, private investment and net export to Indonesia’s economic. The results of this research showed consumption have significant positive to Indonesia’s economic. Government Expenditure, Capitalism stock, Private investment, Net export  have unsignificant impact to indoneisa’s economic. From the results of this research we can suggest to the government give more attentiont indicators that able to support the indonesia’s economic and overcome negative side lowers the indonesia’s economic. And that the government will be able to control the investments made in order to have a positive impact to indonesia’s economic. And also expected for investors to further increase their investment so that increasing employment opportunities and making the indonesia’s economic.